Polyimide composite slurry and preparation method thereof, and polyimide composite structure
The polyimide composite coating prepared by using polyimide composite slurry solves the problem of aging of traditional thermally conductive materials at high temperatures, achieves efficient and stable thermal conductivity, and meets the heat dissipation needs of high-power electronic devices.
Patent Information
- Application Number
- CN202411868874.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
AI Technical Summary
Traditional silicon-based thermally conductive materials will age after high temperatures or long-term operation, resulting in a decrease in heat dissipation efficiency and cannot meet the heat dissipation requirements of higher power electronic devices.
A polyimide composite slurry is provided, including a polyamic acid solution and a dispersion liquid. The polyamide acid solution is composed of a diamine monomer, a dianhydride monomer, a first organic solvent and ultrapure water. The dispersion liquid is composed of a second organic solvent, an inorganic particles, a silane coupling agent, an isocyanate, a dispersant and a defoaming agent. The polyimide composite slurry is prepared by stirring and mixing, and heat curing to form a polyimide composite coating.
The polyimide composite coating has high heat resistance and stability, can maintain performance at high temperatures above 500°C, has high adhesion strength and high thermal conductivity, and can achieve thermal conductivity stably, long-term and fast, ensuring efficient operation of electronic devices.
Smart Images

Figure CN119614067A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a heat conducting material, in particular to a heat conducting material applied to an electronic device to quickly conduct the heat energy generated by the electronic device. Background Art
[0002] Electronic devices generate a lot of heat during high-performance operation. In order to avoid the temperature of the electronic device being too high and the safety protection mechanism being activated, which will limit its performance, thermal conductive silicone grease, thermal conductive silicone, or a composite material thereof is usually applied between the electronic device and the radiator to quickly transfer the heat generated by the electronic device to the radiator for heat dissipation, thereby ensuring that the electronic device can maintain its operational stability and safety when operating at high performance. It is understandable that with the vigorous development of high integration technology, microelectronic packaging technology, high-power LED technology, and supercomputers, the design direction of electronic equipment is gradually developing towards miniaturization, micro-miniaturization, and lightness. In order to achieve higher operating performance, the industry has higher and higher requirements for the heat dissipation of electronic devices. Since traditional silicon-based thermal conductive materials will age after high temperature or long-term operation, and the heat dissipation performance will decrease, they can no longer meet the heat dissipation requirements of higher-power electronic devices. In view of the above-mentioned problems, it is necessary to provide a thermal conductive paste that can adapt to higher temperatures and is more durable. Summary of the invention
[0003] The problem to be solved by the present invention is to provide a thermally conductive material having excellent heat resistance, retention, and thermal conductivity.
[0004] To achieve the above-mentioned object, the present invention provides a polyimide composite slurry, characterized in that it includes: a polyamic acid solution, including: a diamine monomer, a dianhydride monomer, a first organic solvent, and one or more of ultrapure water; a dispersion, including: a second organic solvent, inorganic particles, a silane coupling agent, an isocyanate, a dispersant, or a defoaming agent. The first organic solvent and the second organic solvent are the same or different; the diamine monomer includes: p-phenylenediamine (PDA), 4,4'-diamino The dianhydride monomer comprises one or more of pyromellitic anhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA), 3,3',4,4'-benzophenonetetracarboxylic anhydride (BTDA), or p-phenylene-triphenylene dianhydride (TAHQ).
[0005] More preferably, based on the total weight of the polyamic acid solution, the diamine monomer accounts for 5.5 wt % to 8.5 wt %, and the dianhydride monomer accounts for 9.5 wt % to 12.5 wt %.
[0006] More preferably, the viscosity of the polyamic acid solution is 1000 cP to 5000 cP; or the solid content of the polyamic acid solution is 10 wt % to 18 wt %.
[0007] More preferably, wherein: the inorganic particles comprise: one or more of boron nitride (BN), aluminum oxide (Al2O3), or silicon nitride (Si3N4); the solid content of the dispersion is 5wt% to 10wt%; the dispersion comprises the inorganic particles, and the content of the inorganic particles is 10wt% to 20wt% of the total weight of the solid content contained in the polyamic acid solution; or the dispersion comprises the dispersant and the inorganic particles, and the content of the dispersant is 1wt% to 7wt% of the total weight of the inorganic particles.
[0008] More preferably, the first organic solvent comprises: one or more of dimethylformamide (DMF), dimethylacetamide (DMAc), or N-methylpyrrolidone (NMP).
[0009] More preferably, the second organic solvent comprises: one or more of dimethylformamide (DMF), dimethylacetamide (DMAc), or N-methylpyrrolidone (NMP); the silane coupling agent comprises: one or more of γ-aminopropyltriethoxysilane (silane coupling agent KH-550), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (silane coupling agent KH-560), or γ-methacryloxypropyl (silane coupling agent KH-570); the isocyanate comprises: diphenylmethane diisocyanate (MDI), toluene diisocyanate (TD I), or hexamethylene diisocyanate (HDI); the dispersant comprises: one or more of BYK-9076, BYK-9077, BYK-1165, or BYK-W908; or the defoamer comprises: one or more of GP defoamer, GPES defoamer, T-30C high carbon alcohol defoamer, or polydimethylsiloxane.
[0010] Another object of the present invention is to provide a method for preparing a polyimide composite slurry, characterized in that it comprises: (S1) a polyamic acid solution preparation step, mixing a first organic solvent, a diamine monomer, a dianhydride monomer, and ultrapure water to obtain a polyamic acid solution; (S2) a dispersion liquid preparation step, mixing a second organic solvent, inorganic particles, a silane coupling agent, an isocyanate, a dispersant, and a defoaming agent to obtain a dispersion liquid, wherein the second organic solvent is the same as or different from the first organic solvent; and (S3) a mixing step, stirring and mixing the polyamic acid solution and the dispersion liquid to obtain the polyimide composite slurry.
[0011] More preferably, in the polyamic acid solution preparation step: the first organic solvent, the diamine monomer, the dianhydride monomer, and the ultrapure water are stirred and mixed, and then a polymerization reaction is carried out at a low temperature; or in the dispersion preparation step: the second organic solvent, the inorganic particles, the silane coupling agent, the isocyanate, the dispersant, and the defoaming agent are mixed and ultrasonically shaken.
[0012] More preferably, in the step of preparing the polyamic acid solution: the molar ratio of the diamine monomer to the dianhydride monomer is 1:0.95 to 1.05; the molar number of the ultrapure water is 20% to 40% of the molar number of the diamine monomer; the low temperature is ≤10°C; or the time for the polymerization reaction is 5 to 15 hours; or in the step of preparing the dispersion: the content of the isocyanate is 0.5wt% to 5wt% of the total weight of the solid content contained in the polyamic acid solution; the content of the defoaming agent is 0.5wt% to 5wt% of the total weight of the solid content contained in the polyamic acid solution; the content of the silane coupling agent is 1wt% to 7wt% of the total weight of the solid content contained in the polyamic acid solution; or the ultrasonic oscillation is continuous oscillation at 360W of ultrasonic energy for 0.5 to 2 hours.
[0013] Another object of the present invention is to provide a polyimide composite structure, characterized in that it includes: a substrate; and a polyimide composite coating formed on one side or both sides of the substrate, wherein: the polyimide composite coating is formed by heating and curing a polyimide composite slurry as described above.
[0014] More preferably, the method for forming the polyimide composite coating comprises: coating the polyimide composite slurry on the substrate, and then heating the polyimide composite slurry at a heating rate of 1° C. / min until the temperature reaches 350° C.
[0015] More preferably, the polyimide composite slurry is coated on the substrate by spraying or blade coating.
[0016] More preferably, the thermal conductivity of the polyimide composite coating is greater than 10 W / (m·K); or the adhesion of the polyimide composite coating is 5B as measured by a 100-grid test.
[0017] More preferably, the substrate comprises one or more of an aluminum plate, an aluminum foil, a copper plate, or a copper foil.
[0018] The effectiveness of the present invention over the prior art is that the polyimide composite slurry provided by the present invention can be coated evenly and flatly, so the film surface of the polyimide composite coating formed after curing has high flatness and no bubbles remain in the structure; in addition, the polyimide composite coating has good heat resistance stability and can withstand temperatures of more than 500°C, so it can be ensured that it will not deteriorate at high temperatures and can exert its performance for a long time; in addition, the polyimide composite coating has high adhesion strength and high thermal conductivity, so it can stably, permanently, and quickly achieve a thermal conductivity effect to ensure that electronic devices can operate efficiently. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a flow chart for illustrating the preparation process of polyimide composite slurry;
[0020] Figure 2 It is a planar structural diagram used to illustrate the structural characteristics of the polyimide composite coating. DETAILED DESCRIPTION
[0021] In order to make the above and / or other purposes, effects, and features of the present invention more clearly understood, preferred embodiments are specifically described below in detail:
[0022] The present invention aims to provide a polyimide composite slurry, characterized in that it comprises: a polyamic acid solution, wherein: based on the total weight of the polyamic acid solution, it comprises: 5.5wt% to 8.5wt% of a diamine monomer, and 9.5wt% to 12.5wt% of a dianhydride monomer; the diamine monomer comprises: p-phenylenediamine (PDA), 4,4'-diaminodiphenyl ether (ODA), 1,3-bis(4-aminophenoxy)benzene (TPER), or 4,4'-diamino-2,2'-dimethyl-1,1'-diamino benzene (M-TB), but not limited thereto; and the dianhydride monomer includes: one or more of pyromellitic anhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA), 3,3'4,4'-benzophenonetetracarboxylic anhydride (BTDA), or p-phenylene-triphenylene dianhydride (TAHQ), but not limited thereto; and the dispersion includes: one or more of a second organic solvent, inorganic particles, a silane coupling agent, an isocyanate, a dispersant, or a defoamer, but not limited thereto. In a preferred embodiment, the polyamic acid solution further includes: a first organic solvent, and one or more of ultrapure water, but not limited thereto, wherein: the first organic solvent and the second organic solvent are the same or different. In another preferred embodiment, the first organic solvent includes: one or more of dimethylformamide (DMF), dimethylacetamide (DMAc), or N-methylpyrrolidone (NMP), but not limited thereto.
[0023] Preferably, in order to ensure the coating performance of the polyimide composite slurry, to prevent the generation of bubbles therein, and to improve its adhesion at the same time, so that it can be evenly, permanently, and flatly attached to the substrate 2 or the electronic device; or to improve the heat resistance stability of the polyimide composite slurry to ensure that it will not deteriorate under extremely high temperatures; or to improve the thermal conductivity of the polyimide composite slurry to conduct heat more efficiently and improve the heat dissipation effect for the substrate 2 or the electronic device, wherein: the viscosity of the polyamic acid solution is 1000cP to 5000cP, but not limited thereto; or the solid content of the polyamic acid solution is 10wt% to 18wt%, but not limited thereto. In a preferred embodiment, the inorganic particles include: one or more of boron nitride (BN), aluminum oxide (Al2O3), or silicon nitride (Si3N4), but not limited thereto; the solid content of the dispersion is 5wt% to 10wt%, but not limited thereto; the dispersion contains the inorganic particles, and the content of the inorganic particles is 10wt% to 20wt% of the total weight of the solid content contained in the polyamic acid solution, but not limited thereto; or the dispersion contains the dispersant and the inorganic particles, and the content of the dispersant is 1wt% to 7wt% of the total weight of the inorganic particles, but not limited thereto.
[0024] More preferably, the second organic solvent comprises one or more of dimethylformamide (DMF), dimethylacetamide (DMAc), or N-methylpyrrolidone (NMP), but not limited thereto; the silane coupling agent comprises one or more of γ-aminopropyltriethoxysilane (silane coupling agent KH-550), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (silane coupling agent KH-560), or γ-methacryloxypropyl (silane coupling agent KH-570), but not limited thereto; the isocyanate comprises diphenylmethane diisocyanate (MDI), toluene diisocyanate (TD I), or hexamethylene diisocyanate (HDI), but not limited thereto; the dispersant comprises: one or more of BYK-9076, BYK-9077, BYK-1165, or BYK-W908, but not limited thereto; or the defoamer comprises: one or more of GP defoamer, GPES defoamer, T-30C high carbon alcohol defoamer, or polydimethylsiloxane, but not limited thereto.
[0025] The present invention further provides a method for preparing a polyimide composite slurry, such as Figure 1 As shown, it includes: (S1) a polyamic acid solution preparation step, mixing a first organic solvent, a diamine monomer, a dianhydride monomer, and ultrapure water to obtain a polyamic acid solution; (S2) a dispersion liquid preparation step, mixing a second organic solvent, inorganic particles, a silane coupling agent, an isocyanate, a dispersant, and a defoaming agent to obtain a dispersion liquid, wherein the second organic solvent is the same as or different from the first organic solvent; and (S3) a mixing step, stirring and mixing the polyamic acid solution and the dispersion liquid to obtain the polyimide composite slurry.
[0026] Preferably, in order to ensure the coating performance of the polyimide composite slurry, to prevent the generation of bubbles therein, and to improve its adhesion at the same time, so that it can be evenly, permanently, and flatly attached to the substrate 2 or the electronic device; or to improve the heat resistance stability of the polyimide composite slurry to ensure that it will not deteriorate under extremely high temperatures; or to improve the thermal conductivity of the polyimide composite slurry to conduct heat more efficiently and improve the heat dissipation effect for the substrate 2 or the electronic device, wherein in the polyamic acid solution preparation step: the first organic solvent, the diamine monomer, the dianhydride monomer, and the ultrapure water are stirred and mixed, and then a polymerization reaction is carried out at a low temperature; or in the dispersion preparation step: the second organic solvent, the inorganic particles, the silane coupling agent, the isocyanate, the dispersant, and the defoaming agent are mixed and ultrasonically vibrated. In a preferred embodiment, in the polyamic acid solution preparation step: the molar ratio of the diamine monomer to the dianhydride monomer is 1:0.95 to 1.05, but not limited thereto; the molar number of the ultrapure water is 20% to 40% of the molar number of the diamine monomer, but not limited thereto; the low temperature is ≤10°C, but not limited thereto; or the time for the polymerization reaction is 5 to 15 hours, but not limited thereto; or in the dispersion preparation step: the content of the isocyanate is 0.5wt% to 5wt% of the total weight of the solid content contained in the polyamic acid solution, but not limited thereto; the content of the defoamer is 0.5wt% to 5wt% of the total weight of the solid content contained in the polyamic acid solution, but not limited thereto; the content of the silane coupling agent is 1wt% to 7wt% of the total weight of the solid content contained in the polyamic acid solution, but not limited thereto; or the ultrasonic oscillation is continuous oscillation of 360W of ultrasonic energy for 0.5 to 2 hours, but not limited thereto.
[0027] The present invention further provides a polyimide composite structure, such as Figure 2 As shown, it comprises: a substrate 2; and a polyimide composite coating 1 formed on one side or both sides of the substrate 2, wherein: the polyimide composite coating 1 is formed by heating and curing the polyimide composite slurry as described above.
[0028] More preferably, in order to ensure the coating performance of the polyimide composite coating 1, to prevent the generation of bubbles therein, and to improve its adhesion at the same time, so that it can be evenly, permanently, and flatly attached to the substrate 2 or electronic devices; or to improve the heat resistance stability of the polyimide composite coating 1 to ensure that it will not deteriorate under extremely high temperatures; or to improve the thermal conductivity of the polyimide composite coating 1 to conduct heat more efficiently and improve the heat dissipation effect for the substrate 2 or electronic devices, wherein the method for forming the polyimide composite coating 1 includes: coating the polyimide composite slurry on the substrate 2, and then heating the polyimide composite slurry at a heating rate of 1°C / min until the temperature is raised to 350°C, wherein the temperature can be selectively raised from 25°C, but not limited thereto. In a preferred embodiment, the polyimide composite slurry is applied to the substrate 2 by spraying or scraping, but not limited thereto. In another preferred embodiment, the thermal conductivity of the polyimide composite coating 1 is greater than 10 W / (m·K); or the adhesion of the polyimide composite coating 1 is 5B as measured by a 100-grid test. In another preferred embodiment, the substrate 2 comprises one or more of an aluminum plate, an aluminum foil, a copper plate, or a copper foil, but is not limited thereto.
[0029] In order to illustrate that the polyimide composite coating 1 prepared by different preparation processes and raw material selections has different film surface flatness, heat resistance stability, adhesion strength, or thermal conductivity, the following provides polyimide composite coating 1 samples of Examples 1 to 5 and Comparative Examples 1 to 3, and the preparation conditions and coating properties of each Example and each Comparative Example are summarized in the following Tables 1 to 2.
[0030] 《The following provides Example 1 of the present invention》
[0031] (S1A) Preparation steps of polyamic acid solution: First, build a synthesis reaction device, pass nitrogen into a four-necked reaction flask, and place the four-necked reaction flask in an ice bath to control the reaction temperature T≤10°C; then, add 273.85g of DMF solvent to the four-necked reaction flask, and add 7.03g of PDA and 13.02g of ODA to dissolve for 30min to 60min; then, add 0.47g of ultrapure water to the four-necked reaction flask, and add 19.12g of BPDA and 20.94g of BTDA, and then carry out polymerization reaction at low temperature for 10hr to obtain a polyamic acid solution with a solid content of 17.97wt%;
[0032] (S1 B) Dispersion liquid preparation step: 69.57 g of DMF, 6.058 g of BN, 0.18 g of BYK9076, 0.61 g of GP defoamer, 0.61 g of MDI, and 0.61 g of KH-550 were mixed, and then stirred at high speed for 1 hour using a high-speed disperser, and then shaken for 1 hour using an ultrasonic cleaner to obtain a dispersion liquid;
[0033] (S1 C) a mixing step of mixing 50 g of the polyamic acid solution and 11.25 g of the dispersion, and stirring them sufficiently to obtain a polyimide composite slurry;
[0034] (S1 D) a coating step, spraying the polyimide composite slurry onto the aluminum plate; and
[0035] (S1 E) A heating step, wherein the polyimide composite slurry is heated stepwise from an initial temperature at a rate of 1°C / min until the temperature reaches 350°C to obtain a polyimide composite coating 1 sample.
[0036] 《The following provides Example 2 of the present invention》
[0037] (S2A) Preparation steps of polyamic acid solution: First, build a synthesis reaction device, pass nitrogen into a four-necked reaction flask, and place the four-necked reaction flask in an ice bath to control the reaction temperature T≤10°C; then, add 277.42g of DMF solvent to the four-necked reaction flask, and add 7.03g of PDA and 13.80g of M-TB to dissolve for 30min to 60min; then, add 0.47g of ultrapure water to the four-necked reaction flask, and add 19.12g of BPDA and 20.94g of BTDA, and then carry out polymerization reaction at low temperature for 10hr to obtain a polyamic acid solution with a solid content of 17.97wt%;
[0038] (S2B) Dispersion preparation step: 9.21 g of BN, 0.46 g of BYK9076, 105.92 g of DMF, 1.84 g of GP defoamer, 1.84 g of MDI, and 1.84 g of KH-550 were mixed, and then stirred at high speed for 1 hour using a high-speed disperser, and then shaken for 1 hour using an ultrasonic cleaner to obtain a dispersion;
[0039] (S2C) a mixing step of mixing 50 g of the polyamic acid solution and 11.25 g of the dispersion, and stirring them sufficiently to obtain a polyimide composite slurry;
[0040] (S2D) a coating step of spraying the polyimide composite slurry onto the aluminum plate; and
[0041] (S2E) A heating step, wherein the polyimide composite slurry is heated stepwise from an initial temperature at a rate of 1°C / min until the temperature reaches 350°C to obtain a polyimide composite coating 1 sample.
[0042] 《The following provides Example 3 of the present invention》
[0043] (S3A) Preparation steps of polyamic acid solution: First, a synthesis reaction device is constructed, nitrogen is introduced into a four-necked reaction flask, and the four-necked reaction flask is placed in an ice bath to control the reaction temperature T≤10°C; then, 280.89 g of DMF solvent is added to the four-necked reaction flask, and 16.08 g of TPER and 11.68 g of M-TB are added to dissolve for 30 to 60 min; then, 0.40 g of ultrapure water is added to the four-necked reaction flask, and 16.18 g of BPDA and 17.72 g of BTDA are added, and a polymerization reaction is carried out at low temperature for 10 hours to obtain a polyamic acid solution with a solid content of 17.97 wt%;
[0044] (S3B) Dispersion preparation step: 12.41 g of BN, 0.87 g of BYK9076, 142.62 g of DMF, 3.1 g of GP defoamer, 3.1 g of MDI, and 4.34 g of KH-550 were mixed, and then stirred at high speed for 1 hour using a high-speed disperser, and then shaken for 1 hour using an ultrasonic cleaner to obtain a dispersion;
[0045] (S3C) a mixing step of mixing 50 g of the polyamic acid solution and 11.25 g of the dispersion, and stirring them sufficiently to obtain a polyimide composite slurry;
[0046] (S3D) a coating step of spraying the polyimide composite slurry onto the aluminum plate; and
[0047] (S3E) A heating step, wherein the polyimide composite slurry is heated stepwise from an initial temperature at a rate of 1°C / min until the temperature reaches 350°C to obtain a polyimide composite coating 1 sample.
[0048] The following provides Example 4 of the present invention.
[0049] (S4A) Preparation steps of polyamic acid solution: First, build a synthesis reaction device, pass nitrogen into a four-necked reaction flask, and place the four-necked reaction flask in an ice bath to control the reaction temperature T≤10°C; then, add 283.36g of DMF solvent to the four-necked reaction flask, and add 14.62g of TPER and 10.61g of M-TB to dissolve for 30min to 60min; then, add 0.36g of ultrapure water to the four-necked reaction flask, and add 14.71g of BPDA and 22.92g of TAHQ, and then carry out polymerization reaction at low temperature for 10hr to obtain a polyamic acid solution with a solid content of 17.98wt%;
[0050] (S4B) Dispersion liquid preparation step: 6.32 g of Al2O3, 0.32 g of BYK9076, 72.68 g of DMF, 1.90 g of polydimethylsiloxane, 1.90 g of TDI, and 1.90 g of KH-570 were mixed, and then stirred at high speed for 1 hour using a high-speed disperser, and then shaken for 1 hour using an ultrasonic cleaner to obtain a dispersion liquid;
[0051] (S4C) a mixing step of mixing 50 g of the polyamic acid solution and 11.25 g of the dispersion, and stirring them sufficiently to obtain a polyimide composite slurry;
[0052] (S4D) a coating step of spraying the polyimide composite slurry onto the aluminum plate; and
[0053] (S4E) A heating step is performed to stepwise increase the temperature of the polyimide composite slurry from an initial temperature at a rate of 1°C / min until the temperature reaches 350°C to obtain a polyimide composite coating 1 sample.
[0054] 《The following provides Example 5 of the present invention》
[0055] (S5A) Preparation steps of polyamic acid solution: First, build a synthesis reaction device, pass nitrogen into a four-necked reaction flask, and place the four-necked reaction flask in an ice bath to control the reaction temperature T≤10°C; then, add 263.46g of DMF solvent to the four-necked reaction flask, and add 13.15g of TPER and 9.55g of M-TB to dissolve for 30min to 60min; then, add 0.32g of ultrapure water to the four-necked reaction flask, and add 14.50g of BTDA and 20.62g of TAHQ, and then carry out polymerization reaction at low temperature for 10hr to obtain a polyamic acid solution with a solid content of 17.97wt%;
[0056] (S5B) Dispersion liquid preparation step: 8.72 g of Al2O3, 0.61 g of BYK9076, 100.28 g of DMF, 2.91 g of GP defoamer, 2.91 g of TDI, and 4.07 g of KH-570 were mixed, and then stirred at high speed for 1 hour using a high-speed disperser, and then shaken for 1 hour using an ultrasonic cleaner to obtain a dispersion liquid;
[0057] (S5C) a mixing step of mixing 50 g of the polyamic acid solution and 11.25 g of the dispersion, and stirring them sufficiently to obtain a polyimide composite slurry;
[0058] (S5D) a coating step of spraying the polyimide composite slurry onto the aluminum plate; and
[0059] (S5E) A heating step, wherein the polyimide composite slurry is heated stepwise from an initial temperature at a rate of 1°C / min until the temperature reaches 350°C to obtain a polyimide composite coating 1 sample.
[0060] The following is a comparative example 1 of the present invention.
[0061] (S6A) Preparation steps of polyamic acid solution: first, build a synthesis reaction device, introduce nitrogen into a four-necked reaction flask, and place the four-necked reaction flask in an ice bath to control the reaction temperature T≤10°C; then, add 273.85g of DMF solvent into the four-necked reaction flask, and add 7.03g of PDA and 13.02g of ODA to dissolve for 30min to 60min; then, add 0.47g of ultrapure water into the four-necked reaction flask, and add 19.12g of BPDA and 20.94g of BTDA, and then carry out polymerization reaction at low temperature for 10hr to obtain a polyamic acid solution with a solid content of 17.97wt%;
[0062] (S6B) a coating step of spraying the polyamic acid solution onto the aluminum plate; and
[0063] (S6C) A heating step in which the polyamic acid solution is heated stepwise from an initial temperature at a rate of 1°C / min until the temperature reaches 350°C to obtain a polyimide composite coating 1 sample.
[0064] The following provides a comparative example 2 of the present invention.
[0065] (S7A) Preparation steps of polyamic acid solution: first, build a synthesis reaction device, introduce nitrogen into a four-necked reaction flask, and place the four-necked reaction flask in an ice bath to control the reaction temperature T≤10°C; then, add 273.85g of DMF solvent into the four-necked reaction flask, and add 7.03g of PDA and 13.02g of ODA to dissolve for 30min to 60min; then, add 19.12g of BPDA and 20.94g of BTDA into the four-necked reaction flask, and perform a polymerization reaction at low temperature for 10hr to obtain a polyamic acid solution with a solid content of 17.99wt%;
[0066] (S7B) a coating step of spraying the polyamic acid solution onto the aluminum plate; and
[0067] (S7C) A heating step in which the polyamic acid solution is heated stepwise from an initial temperature at a rate of 1°C / min until the temperature reaches 350°C to obtain a polyimide composite coating 1 sample.
[0068] The following provides comparative example 3 of the present invention.
[0069] (S8A) Preparation steps of polyamic acid solution: first, build a synthesis reaction device, pass nitrogen into a four-necked reaction flask, and place the four-necked reaction flask in an ice bath to control the reaction temperature T≤10°C; then, add 273.85g of DMF solvent to the four-necked reaction flask, and add 7.03g of PDA and 13.02g of ODA to dissolve for 30min to 60min; then, add 0.47g of ultrapure water to the four-necked reaction flask, and add 19.12g of BPDA and 20.94g of BTDA, and then carry out polymerization reaction at low temperature for 10hr to obtain a polyamic acid solution with a solid content of 17.97wt%;
[0070] (S8B) Dispersion liquid preparation step: 17.45 g of Al2O3, 0.61 g of BYK9076, 100.28 g of DMF, 2.91 g of GP defoamer, 2.91 g of TDI, and 4.07 g of KH-570 were mixed, and then stirred at high speed for 1 hour using a high-speed disperser, and then shaken for 1 hour using an ultrasonic cleaner to obtain a dispersion liquid;
[0071] (S8C) a mixing step of mixing 50 g of the polyamic acid solution and 33.75 g of the dispersion, and stirring them sufficiently to obtain a polyimide composite slurry;
[0072] (S8D) a coating step of spraying the polyimide composite slurry onto the aluminum plate; and
[0073] (S8E) A heating step, wherein the polyimide composite slurry is heated stepwise from an initial temperature at a rate of 1°C / min until the temperature reaches 350°C to obtain a polyimide composite coating 1 sample.
[0074] Table 1. Raw materials, process, and coating properties of the polyimide composite coating 1 samples of Examples 1 to 5
[0075]
[0076]
[0077] Table 2. Raw materials, process, and coating properties of the polyimide composite coating 1 samples of Comparative Examples 1 to 3
[0078]
[0079]
[0080]
[0081] The effectiveness of the present invention over the prior art is that the polyimide composite slurry provided by the present invention can be coated evenly and flatly, so the film surface of the polyimide composite coating 1 formed after curing has high flatness and no bubbles remain in the structure; in addition, the polyimide composite coating 1 has good heat resistance and stability, and can withstand temperatures above 500°C, so it can be ensured that it will not deteriorate at high temperatures and can exert its performance for a long time; in addition, the polyimide composite coating 1 has high adhesion strength and high thermal conductivity, so it can stably, permanently, and quickly achieve a thermal conductivity effect to ensure that electronic devices can operate efficiently.
[0082] However, what is described above is only a preferred embodiment of the present invention, but it cannot be used to limit the patent protection scope of the present invention; therefore, all simple equivalent changes and modifications made according to the patent protection scope of the present invention and the contents of the specification still fall within the patent protection scope of the present invention.
Claims
1. A polyimide composite slurry, characterized in that: These include: A polyamic acid solution comprising: one or more of a diamine monomer, a dianhydride monomer, a first organic solvent, and ultrapure water; The dispersion includes: one or more of a second organic solvent, inorganic particles, a silane coupling agent, an isocyanate, a dispersant, or a defoaming agent; The first organic solvent and the second organic solvent are the same or different; The diamine monomer comprises: one or more of p-phenylenediamine (PDA), 4,4'-diaminodiphenyl ether (ODA), 1,3-bis(4-aminophenoxy)benzene (TPER), or 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl (M-TB); The dianhydride monomer includes one or more of pyromellitic anhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylic anhydride (BPDA), 3,3'4,4'-benzophenonetetracarboxylic anhydride (BTDA), or p-phenylene-trimethylene dianhydride (TAHQ).
2. The polyimide composite slurry according to claim 1, characterized in that: The polyimide composite slurry according to claim 1 is characterized in that, based on the total weight of the polyamic acid solution, the diamine monomer is 5.5wt% to 8.5wt%, and the dianhydride monomer is 9.5wt% to 12.5wt%.
3. The polyimide composite slurry according to claim 1, characterized in that: in: The viscosity of the polyamic acid solution is 1000 cP to 5000 cP; or The solid content of the polyamic acid solution is 10 wt % to 18 wt %.
4. The polyimide composite slurry according to claim 1, characterized in that: in: The inorganic particles include: one or more of boron nitride (BN), aluminum oxide (Al2O3), or silicon nitride (Si3N4); The solid content of the dispersion is 5wt% to 10wt%; The dispersion contains the inorganic particles, and the content of the inorganic particles is 10wt% to 20wt% of the total weight of the solid content contained in the polyamic acid solution; or The dispersion liquid contains the dispersant and the inorganic particles, and the content of the dispersant is 1 wt % to 7 wt % of the total weight of the inorganic particles.
5. The polyimide composite slurry according to claim 2, characterized in that: The first organic solvent comprises: one or more of dimethylformamide (DMF), dimethylacetamide (DMAc), or N-methylpyrrolidone (NMP).
6. The polyimide composite slurry according to claim 1, characterized in that: The second organic solvent comprises: one or more of dimethylformamide (DMF), dimethylacetamide (DMAc), or N-methylpyrrolidone (NMP); The silane coupling agent comprises: one or more of γ-aminopropyltriethoxysilane (silane coupling agent KH-550), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (silane coupling agent KH-560), or γ-methacryloxypropyl (silane coupling agent KH-570); The isocyanate comprises: one or more of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), or hexamethylene diisocyanate (HDI); The dispersant comprises: one or more of BYK-9076, BYK-9077, BYK-1165, or BYK-W908; or The defoaming agent comprises: one or more of GP defoaming agent, GPES defoaming agent, T-30C high carbon alcohol defoaming agent, or polydimethylsiloxane.
7. A method for preparing a polyimide composite slurry, characterized in that: It includes: (S1) a polyamic acid solution preparation step of mixing a first organic solvent, a diamine monomer, a dianhydride monomer, and ultrapure water to obtain a polyamic acid solution; (S2) a dispersion preparation step of mixing a second organic solvent, inorganic particles, a silane coupling agent, an isocyanate, a dispersant, and a defoaming agent to obtain a dispersion, wherein the second organic solvent is the same as or different from the first organic solvent; and (S3) A mixing step of stirring and mixing the polyamic acid solution and the dispersion to obtain the polyimide composite slurry.
8. The method according to claim 7, characterized in that: In the polyamic acid solution preparation step: the first organic solvent, the diamine monomer, the dianhydride monomer, and the ultrapure water are stirred and mixed, and then a polymerization reaction is carried out at a low temperature; or In the dispersion preparation step, the second organic solvent, the inorganic particles, the silane coupling agent, the isocyanate, the dispersant, and the defoaming agent are mixed and ultrasonically shaken.
9. The method according to claim 8, characterized in that: In the polyamic acid solution preparation step: The molar ratio of the diamine monomer to the dianhydride monomer is 1:0.95 to 1.05; The molar number of the ultrapure water is 20% to 40% of the molar number of the diamine monomer; The low temperature is ≤10°C; or The polymerization reaction is carried out for 5 to 15 hours; or In the dispersion preparation step: The content of the isocyanate is 0.5wt% to 5wt% of the total weight of the solid content contained in the polyamic acid solution; The content of the defoamer is 0.5wt% to 5wt% of the total weight of the solid content contained in the polyamic acid solution; The content of the silane coupling agent is 1wt% to 7wt% of the total weight of the solid content contained in the polyamic acid solution; or The ultrasonic vibration is continuous vibration at 360W of ultrasonic energy for 0.5 to 2 hours.
10. A polyimide composite structure, characterized in that: Include: a substrate; and A polyimide composite coating is formed on one side or both sides of the substrate, wherein the polyimide composite coating is formed by heating and curing a polyimide composite slurry as described in any one of claims 7 to 9.
11. The polyimide composite structure according to claim 10, characterized in that: The method for forming the polyimide composite coating comprises: coating the polyimide composite slurry on the substrate, and then heating the polyimide composite slurry at a heating rate of 1° C. / min until the temperature reaches 350° C.
12. The polyimide composite structure according to claim 11, characterized in that: The polyimide composite slurry is coated on the substrate by spraying or scraping.
13. The polyimide composite structure according to claim 10, characterized in that: The thermal conductivity of the polyimide composite coating is greater than 10 W / (m·K); or The adhesion of the polyimide composite coating is measured by a 100-grid test and the value is 5B.
14. The polyimide composite structure according to claim 10, characterized in that: The substrate includes one or more of an aluminum plate, an aluminum foil, a copper plate, or a copper foil.